JAKARTA CREATIVE HUB - Putri, Aviannisa
The development of world’s and Indonesia’s economy has been greatly influenced by the emergence of the creative class, people who are capable of increasing the economic value by a factor called ‘creativity’. In Indonesia, the rise of the creative economy and industry has been one of the strategies of the growing economy’s development, which leads to the establishment of Badan Ekonomi Kreatif (Bekraf) which holds responsibility as a business incubator for Indonesia’s creative industry people. This fictional project takes place in Kampung Bandan Street, North Jakarta, an area that is underoing a physical degradation. As stated in the DKI Jakarta RTRW, this area is included in the Prioritazion of Regional Embodiment process as an area developing the function of an exhibition and business information center. Jakarta Creative Hub aims to create a creation space with various functions that could accommodate the number of creative industry’s subsectors and contribute to the development of Indonesia’s creative economy. This building is divided to five main districts which are the exhibition district, commercial district, creation district, knowledge district, business district, along with open spaces accessible to the public. In realization of the mission and aims of the project, a concept of Creative Village is chosen with the main issue of flexibility. Modules of precast concrete frames and kontainers are one of the strategies to answer the issue. The use of kontainer units also acts as a reflection and to strengthen the area’s image, which has been well known for its kontainer yard and Kampung Bandan Train Station. A building with a total area of 10,000 sqm is built above a 15,510 sqm site, expanding vertically up to four floors. The open spaces are designed as a sequence and the human scale labyrinths which connects one public open space to another.